If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -1(2y + -5y) = 29 Combine like terms: 2y + -5y = -3y 6y + -1(-3y) = 29 Remove parenthesis around (-3y) 6y + -1 * -3y = 29 Multiply -1 * -3 6y + 3y = 29 Combine like terms: 6y + 3y = 9y 9y = 29 Solving 9y = 29 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '9'. y = 3.222222222 Simplifying y = 3.222222222
| 1.48(k+3)=5.92 | | b+14=1 | | d+(-7)=12 | | 6x+3=98-3x+6 | | 7+1-6x+3x=3x-5x | | q+6.44=0.72 | | k+18=32 | | -p+7=13 | | 5(-2v+6)-4v=-2(v-3) | | 7.2=1.8x | | -2*-0.36=x | | -20=a-8 | | 7.1=x-1.4 | | -2.65(g-10)=-15.9 | | 2a^2-6a+13=0 | | v-19=-36 | | 17.6=3.9(p+3)+2 | | -8h=-48 | | 15m+4+9m=-32 | | 5(3x-9)-2=5(x-3)+28 | | -8=-5+n | | w+175=98 | | 9x-(3x-7)=25 | | 13-16g+4g=25 | | 46=2(12)+2(b) | | a-7=-26 | | (x-5)(x^2-11x+28)=0 | | 3y-8x=17 | | 113=276-q | | 5e^8t=6e^7t | | 8-3(x+1)=20 | | 15x+x-12=63 |